THE EFFECTIVENESS OF STORYTELLING TO IMPROVE WITH DESCRIPTIVE TEXT OF STUDENTS’ READING ACHIEVEMENT - Melika, Della; Iman, Jaya Nur; Ulfah, Badriyah (Global Expert: Jurnal Bahasa dan Sastra, 2023)
Storytelling is the process of someone conveying and receiving a story through various media, such as words, pictures or sound. Therefore, it can be said that storytelling can improve students' reading skills. This study aims to examine whether the story telling learning method is effective in improving students' reading skills. Researchers conducted research at SMP Negeri 3 Palembang Class VII.10 with a total of 31 students. Using pre-test and post-test designs as pre-experimental procedures, data collection techniques used in this study were pre-test and post-test. Then the data was tested with a normality test of 0.00 less than 0.05 (0.00 <0.05). Then all pre and post test data are normally distributed. From the results of the analysis of single paired t-test data, it can be seen that the results of the t-analysis obtained -7,803 df 30 significance value for the control group 0.000 H0 was rejected He was accepted, t was obtained for the experimental group -14.351 df 30 for the experimental group a significance value of 0.000 H0 was rejected Accepted independent t-test with a t-test of 10.015 df 60 and a significance value of 2 with 0.000. It can be concluded that telling stories can increase vocabulary in class VII.10 of SMP Negeri 3 Palembang, and this research shows that students always increase their English vocabulary because vocabulary plays an important role in everyday life.